2021
DOI: 10.1155/2021/1370862
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Melatonin Attenuates Cardiac Ischemia‐Reperfusion Injury through Modulation of IP3R‐Mediated Mitochondria‐ER Contact

Abstract: Although the interplay between mitochondria and ER has been identified as a crucial regulator of cellular homeostasis, the pathogenic impact of alterations in mitochondria-ER contact sites (MERCS) during myocardial postischemic reperfusion (I/R) injury remains incompletely understood. Therefore, in our study, we explored the beneficial role played by melatonin in protecting cardiomyocytes against reperfusion injury via stabilizing mitochondria-ER interaction. In vitro exposure of H9C2 rat cardiomyocytes to hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…In addition, an overload of Ca 2+ leading to oxidative metabolism impairment and ROS overproduction [ 123 ]. Previous studies have suggested that under oxygen stress, ROS produced by mitochondria will cause membrane lipid peroxidation and changes in mitochondrial function, resulting in the release of Ca 2+ and apoptosis of mitochondria [ 124 ]; (3) ROS can regulate IP 3 R production and affect Ca 2+ release from the ER into mitochondria [ 125 ]; (4) ROS can also affect the sarcoplasmic reticulum Ca 2+ pump and inhibit intracellular or extracellular ER Ca 2+ transfer by inhibiting the Ca 2+ -ATPase pump [ 126 ]; (5) Both ROS and Ca 2+ can induce MPTP opening. On the other hand, MPTP opening leads to a large increase in ROS [ 127 ].…”
Section: Mitochondrial Ca 2+ and Tumor Cell Apoptosismentioning
confidence: 99%
“…In addition, an overload of Ca 2+ leading to oxidative metabolism impairment and ROS overproduction [ 123 ]. Previous studies have suggested that under oxygen stress, ROS produced by mitochondria will cause membrane lipid peroxidation and changes in mitochondrial function, resulting in the release of Ca 2+ and apoptosis of mitochondria [ 124 ]; (3) ROS can regulate IP 3 R production and affect Ca 2+ release from the ER into mitochondria [ 125 ]; (4) ROS can also affect the sarcoplasmic reticulum Ca 2+ pump and inhibit intracellular or extracellular ER Ca 2+ transfer by inhibiting the Ca 2+ -ATPase pump [ 126 ]; (5) Both ROS and Ca 2+ can induce MPTP opening. On the other hand, MPTP opening leads to a large increase in ROS [ 127 ].…”
Section: Mitochondrial Ca 2+ and Tumor Cell Apoptosismentioning
confidence: 99%
“…Application of melatonin inhibits IP3R, stabilizing the physical contacts between mitochondria and ER, and thus improving mitochondrial function and reducing cardiomyocytes damage. Moreover, some other MAM markers, Fis1, BAP31, and MFN2, were also inhibited by melatonin [ 100 ]. These data suggest that melatonin-induced cardioprotective effect is mediated via normalization of mitochondria-ER interaction.…”
Section: Mams Targeting As a Potential Therapeutic Strategymentioning
confidence: 99%
“…Remarkably, melatonin exerts cardioprotective effects in several cardiovascular disorders (Zhou et al, 2018). Furthermore, melatonin is protective against cardiomyocyte I/R injury by stabilizing MERCs, modulating gene expression, and mediating mitochondrial protection by preventing the positive regulation of the IP3R in I/R (Li et al, 2021).…”
Section: Mitochondria-er Contacts and Cardiomyocytesmentioning
confidence: 99%